2003
DOI: 10.1007/s00792-002-0295-2
|View full text |Cite
|
Sign up to set email alerts
|

Halomonas glaciei sp. nov. isolated from fast ice of Adelie Land, Antarctica

Abstract: Eleven psychrophilic bacteria were isolated from a solid layer of fast ice in the middle of Pointe-Geologie Archipelago, Adelie Land, Antarctica. The 11 isolates based on the phenotypic characteristics, chemotaxonomic and phylogenetic analysis have been identified as members of the genus Halomonas. All the isolates at the 16S rDNA sequence level were identical, possessed the 15 conserved nucleotides of the family Halomonadaceae and four nucleotides of the genus Halomonas. Therefore, the 16S rDNA sequence of DD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
35
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 34 publications
4
35
0
Order By: Relevance
“…Most bacteria isolated from sea ice have been found to be pigmented and highly coldadapted, with both free-living and epiphytic bacteria present (Grossi et al 1984). Most taxa isolated from sea ice belong to the γ-proteobacteria and the CytophagaFlavobacterium-Bacteroides division (Bowman et al 1997, Gozink et al 1998, Junge et al 1998, Nichols et al 1999, Reddy et al 2002. 16S rDNA clone library analysis corroborated these culture data (Brown & Bowman 2001).…”
mentioning
confidence: 86%
“…Most bacteria isolated from sea ice have been found to be pigmented and highly coldadapted, with both free-living and epiphytic bacteria present (Grossi et al 1984). Most taxa isolated from sea ice belong to the γ-proteobacteria and the CytophagaFlavobacterium-Bacteroides division (Bowman et al 1997, Gozink et al 1998, Junge et al 1998, Nichols et al 1999, Reddy et al 2002. 16S rDNA clone library analysis corroborated these culture data (Brown & Bowman 2001).…”
mentioning
confidence: 86%
“…Twenty-four species of Halomonas have been described at the time of writing (Arahal et al, 2002a, b;Heyrman et al, 2002;Yoon et al, 2002;Romanenko et al, 2002;Reddy et al, 2003). The strains analysed here are the first to be characterized from the deep sea and from hydrothermalvent habitats.…”
mentioning
confidence: 94%
“…Phenotypic tests revealed that the isolates were physiologically versatile and tended to have more traits in common with each other than with closely related Halomonas species, presumably a reflection of their common deep-sea, hydrothermal-vent habitat of origin. The G+C content of the DNA for all strains was 56?0-57?6 mol%, and DNA-DNA hybridization experiments revealed that four strains (Eplume1 Halophilic and halotolerant micro-organisms are typically isolated from hypersaline environments such as lagoons, saline and haloalkaline lakes (the Dead Sea, Great Salt Lake, thalassohaline Antarctic lakes, African rift soda lakes), artificial salterns, cured and salty foods, briny petroleum reservoirs, hypersaline desert soils and sea ice (Ventosa et al, 1982(Ventosa et al, , 1998Vreeland et al, 1980;Quesada et al, 1984;Franzmann et al, 1987a;James et al, 1990;Valderrama et al, 1991;Adkins et al, 1993;Duckworth et al, 1996 Duckworth et al, , 2000 Bowman et al, 1997;Satomi et al, 1997; Mormile et al, 1999;Bouchotroch et al, 2001;Yoon et al, 2002;Reddy et al, 2003). They have also recently been found in the very dry environment of the walls and murals of a Details of growth rates of the novel isolates under varying temperatures and salt concentrations, transmission electron micrographs of cells and a 16S rDNA-based maximum-likelihood tree including a wider range of reference species are available as supplementary material in IJSEM Online.…”
mentioning
confidence: 99%
“…Strain T5301 exhibited the highest levels of identity (96.3-99.6%) (Pearson and Lipman, 1988) to the 5 Halomonas species, which were isolated from antarctic fast and pack ice samples (Brinkmeyer et al, 2003;Reddy et al, 2003), marine water samples in Hawaii (Arahal et al, 2002), and hypersaline lakes in Antarctica (Arahal et al, 2002). Strain T5301 belonged to a branch of psychrophilic antarctic strains, H. variabilis strain ANT9112 and H. glaciei strain DD39 T (Fig.…”
mentioning
confidence: 99%